Literasi Pencegahan Stunting melalui Edukasi Kesehatan dan Demonstrasi Terapi Komplementer pada Ibu Menyusui: Stunting Prevention Literacy through Health Education and Demonstration of Complementary Therapy in Breastfeeding Mother - Puspitasari, Nike Arta; Yuliani, Anita; Assidik, Qarrin Nafisya Rabbany (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Most villages in Bandung Regency still experience a high prevalence of stunting. Because of this, ten villages spread across eight sub-districts in this area are a priority for handling stunting. In Katapang Village, the coverage of stunted toddlers in 2021 is 13.09%, and is a village with a stunting locus. Research conducted in 2022 shows that only 36.9% of babies receive exclusive breast milk in children with stunting status in Katapang Village, Bandung Regency. This activity aims to empower breastfeeding mothers independently in preventive efforts to prevent stunting in children. The method used is providing health education demonstrations and practical work on one of the complementary therapies to increase breast milk production, namely oxytocin massage. The fundamental contribution of this activity is that a chain of information is formed for breastfeeding mothers through information media that can be disseminated to the community. In the activity, a direct output evaluation of the activity was carried out by knowing that there was an increase in pre-test and post-test results after being given Health Education material. The results of the increase in pre-test and post-test results were 27%. Evaluation of the implementation of oxytocin massage practice is the mother's ability to perform oxytocin massage independently correctly.